Geographically Weighted Poisson Regression dengan Fungsi Pembobot Kernel Gaussian untuk Pemodelan Jumlah Kematian Bayi di Jawa Barat pada Tahun 2019 - Mestika Meytiara; Anneke Iswani Achmad (Bandung Conference Series: Statistics, 2022)
Abstract. Regression analysis is a statistical analysis that aims to model the relationship between independent variables with dependent variables. If the independent variable is Poisson-distributed then the regression model used is Poisson regression. Geographically Weighted Poisson Regression (GWPR) is a local form of Poisson regression where the location of data collection is considered. In this study, Geographically Weighted Poisson Regression (GWPR) will be used to model the number of infant mortality in West Java in 2019 using the Gaussian kernel weighting function. This study aims to obtain a model of the number of infant mortality in West Java Province in 2019 and find out what factors affect the number of infant mortality in West Java Province in 2019. Based on the value of Akaike's Information Criterion (AIC), it is known that the GWPR model with the Gaussian kernel weighting function is more accurate than the Poisson regression model because it has the smallest AIC value. Abstrak. Analisis regresi adalah suatu analisis statistik yang bertujuan untuk memodelkan hubungan antara variabel bebas dengan variabel terikat. Apabila variabel bebas berdistribusi Poisson maka model regresi yang digunakan adalah regresi Poisson. Geographically Weighted Poisson Regression (GWPR) merupakan bentuk lokal dari regresi Poisson dimana lokasi pengambilan data sangat diperhatikan. Dalam penelitian ini akan digunakan Geographically Weighted Poisson Regression (GWPR) untuk memodelkan jumlah kematian bayi di Jawa Barat pada tahun 2019 dengan menggunakan fungsi pembobot kernel Gaussian. Penelitian ini bertujuan untuk mendapatkan model jumlah kematian bayi di Provinsi Jawa Barat pada tahun 2019 serta mengetahui faktor-faktor apa saja yang mempengaruhi jumlah kematian bayi di Provinsi Jawa Barat pada tahun 2019. Berdasarkan nilai Akaike’s Information Criterion (AIC), diketahui bahwa model GWPR dengan fungsi pembobot kernel Gaussian lebih akurat dibandingkan model regresi Poisson karena memiliki nilai AIC terkecil.